Cord pilot trial: update to randomised trial protocol. Issue 1 (December 2015) - Bradshaw, Lucy; Pushpa-Rajah, Angela; Dorling, Jon; Mitchell, Eleanor; Duley, Lelia
Abstract Background The Cord Pilot Trial aimed to assess the feasibility of conducting a large UK randomised trial to compare the effects of alternative polices for timing of cord clamping (immediate within 20 seconds or deferred after at least 2 minutes) for very preterm birth before 32 weeks gestation. Initial recruitment was from March 2013 to February 2014, phase 2 was from March 2014 to February 2015. This paper updates the pilot trial protocol (Trials 15(1):258, 2014) and presents the changes for phase 2. Methods An electronic randomisation system was introduced at three of the eight pilot sites. For follow-up of children, the Parent Report of Children's Abilities – Revised (PARCA-R) will not be used. For children recruited to the trial during phase 2, follow-up at age 2 years (corrected for gestation at birth) will be by parent completed Ages and Stages Questionnaire (Squire J, Ages and Stages Questionnaires (ASQ), 2009) alone unless funds can be secured for the additional Bayley Scales of Infant Development III (Bayley N, Bayley Scales of Infant and Toddler Development, Third Edition. (Bayley-III), 2005) assessments. To assess accuracy of the cranial ultrasound diagnosis of intraventricular haemorrhage: (i) quality of the scans will be assessed using the British Society of Paediatric Radiology recommendations, and (ii) scan results will be confirmed by independent adjudication. Within and between adjudicator reliability will be assessed. In addition to the analyses planned to assess feasibility of the full trial based on data from the first year of recruitment, data on compliance and outcomes will be presented by allocated group for all women and babies recruited. Trial registration ISRCTN21456601, registered on 28 February 2013.